Copper(II) benzoates and acetates with 2-aminopyridine - Kozlevčar, Bojan (Acta chimica slovenica, 2001)
Two monomeric and two dimeric copper(II) benzoate and acetate coordination compounds with 2-aminopyridine were synthesized. The crystal structures of benzoate compounds were determined by X-ray diffraction analyses. The monomeric benzoate form ?$Cu(O_2CC_6H_5)_2(2apy)_2$?(2apy=2-aminopyridine) is composed of trans oriented ligands around central copper(II) atom, where benzoates acts as asymmetrical chelates (Cu-O 1.97 and 2.65 L). On the other hand, dimeric form ?$Cu_2(O_2CC_6H_5)_4(apy)_2$? reveals paddle - wheel type structure where 2-aminopyridine acts as axial ligand via pyridine nitrogen atom. All compounds were characterized by standard physico-chemical methods and tested for their fungal mycelial growth retardation activity for wood fungi Tremetes versicolor and Antrodia vaillantii.
Keywords: bakrove spojine; IR spektroskopija; koordinacijske spojine; rentgenska difrakcija; struktura